Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1074/jbc.m110.176156
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ubiquitylation of the Epithelial Na+ Channel Controls Extracellular Proteolytic Channel Activation via Conformational Change

Abstract: The epithelial Na

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 36 publications
3
25
2
Order By: Relevance
“…33, 34 However we observed similar effects on cleavage products with a Liddle's mutant b-subunit in which ubiquitination is at least partially disrupted. Other possible mechanisms include Na C -dependent changes in the activity of proteases, 14 or preferential retrieval of specific cleaved products of ENaC from the cell surface.…”
supporting
confidence: 55%
“…33, 34 However we observed similar effects on cleavage products with a Liddle's mutant b-subunit in which ubiquitination is at least partially disrupted. Other possible mechanisms include Na C -dependent changes in the activity of proteases, 14 or preferential retrieval of specific cleaved products of ENaC from the cell surface.…”
supporting
confidence: 55%
“…Maintained diurnal rhythm of Na ϩ and K ϩ excretion in Usp2-KO mice. As it was previously proposed that USP2-45 is an aldosterone-induced protein in the kidney, able to stimulate ENaC expression and activity in heterologous expression systems, including Xenopus laevis oocytes, renal epithelial cells (mpkCCD cl4 cells) and Hek293 cells (14,44,45), we were interested to know whether Usp2-KO mice are defective in the regulation of Na ϩ homeostasis and other related renal parameters. Because USP2-45 protein is highly rhythmic, we housed mice in metabolic cages for 24 h and recorded water and food intake, urine volume, and creatinine excretion every 4 h around the clock (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because we had previously shown that heterologous expression of USP2-45 regulates ENaC (14,44,45), we were wondering whether there is some compensation by proteins involved in ubiquitylation/deubiquitylation or in the control of Na ϩ homeostasis. We therefore carried out gene expression profiling of total kidneys of control or KO mice, using Affymetrix oligonucleotide arrays.…”
Section: Suppression Of Usp2 Is Not Compensated By Proteins Involved mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that the balance of ubiquitination/deubiquitination of ENaC N termini is coupled to the efficiency of proteolysis of the extracellular domain (11)(12)(13). It is hypothesized that ubiquitination of the cytosolic N termini controls the accessibility of cleavage sites in the extracellular domain to channel-activating proteases through conformational changes that propagate along the length of the channel.…”
mentioning
confidence: 99%